Diverse slip behavior of the Banyak Islands subsegment of the Sunda megathrust in Sumatra, Indonesia - Morgan, Paul M. (2021)
Nearly every type of slip behavior of which megathrusts are known to be capable of has been observed within a narrow ~75-km-wide strip of the Sunda megathrust—the Banyak Islands subsegment. The diverse list of recorded slip events starts with the great 1861 M  ~ 8.5 earthquake and includes the 1907 M  ~ 8.2 shallow tsunami earthquake, the 1966–1981 slow slip event, the great 2005 M 8.6 Nias-Simeulue earthquake and associated afterslip, many small (M < 6) to moderate (6 ≤ M < 7) earthquakes, and the large 6 April 2010 M 7.8 Banyak Islands earthquake. In this paper we map out the spatial and temporal relationships between these slip events to search for a pattern and possible controls on slip behavior. We use GPS and coral geodetic data to derive a coseismic slip distribution for the relatively understudied 2010 event and find that this event fits like a puzzle piece into a low slip patch left by the 2005 event. We compare the recent slip sequence with the historical sequence associated with the 1861 event and find that the modern slip pattern could be a repeat of the historical slip pattern, possibly suggesting the importance of stationary fault properties in controlling slip. The diverse set of slip events mostly fit our expectations within depth-dependent rupture zones; however, the overlaps between events of different slip types may complicate this conceptual model. Along strike, we suggest that a subducting fracture zone could act to diversify the slip behavior, and we explore possible mechanisms for this slip control.